Kontribusi Matematika dalam Konteks Fikih - Muniri, Muniri (Institut Agama Islam Negeri (IAIN) Tulungagung, 2016)
Indeed, it was inevitable that there is a correlation between religion and mathematics. It is shown that the relationship between the science of religion based on the Qurâan with science and mathematics. Mathematical understanding by most people is known as an exact science. Certainty in mathematics is defined as a clear. Meaning, there are clear rules, regulations, laws, formulas, and steps that are logical. Similarly, in fiqh (Islamic law) also governs the conduct and governance of worship which clearly and unequivocally based on the arguments described by the Qurâan to the Prophet Muhammad S.A.W. Hadith form. Thus, based on the similarity of the nature and character of course mathematics has contributed positively to the context of jurisprudence which became amaliah Muslims in daily life, for example, in determining the amount of water two kulah, counting prayers, calculating zakat, the division of inheritance rights, counting favors (reward), and so forth. Whether consciously or not, the presence of mathematics provides a significant contribution by helping to make it easier to resolve the problem through the formulation of instructions or a simple formula. The objective is to study on the contribution of mathematics in the context of fiqh.